Lactic Acid Bacteria Isolated From Digestive Tract of Broilers Treated with Fish Protein Hydrolysate - Esti Utarti; Eva Tyas Utami; Achmad Sjaifullah; Wuryanti Handayani; Malika Belkis; Rani Dian Medayani (Jurnal Biodjati, 2025)
The composition of the feed plays a role in stimulating the activity of the microbiota in the gastrointestinal tract; therefore, the addition of fish protein hydrolysate (FPH) is suspected to influence the activity of microbiota, especially probiotics. Therefore, the presence of probiotics in the gastrointestinal tract affects the weight and quality of the broiler. This research aims to investigate the effect of administering fish protein hydrolysate as a dietary supplement on the composition of lactic acid bacteria (LAB), a potential probiotic candidate. This research was conducted in several stages, including the diversification of feeding broilers, the isolation and purification of LAB from the caecum and small intestine, primary characteristics, pathogenicity tests, and biochemical identification of LAB. Feed diversification was conducted by supplementing diets with 1%, 1.5%, and 2% FPH in 20-day-old for 7 days.. LAB from the small intestine and caecum samples were isolated on MRSA media by adding CaCO3. The Gram test, catalase test, and endospore staining test were carried out to characterize the suspected LAB primarily. The pathogenicity test was conducted by inoculating LAB on blood agar medium. Furthermore, biochemical tests are carried out using the KB020 kit. The results showed that the highest population of LAB in the small intestine (1.57 × 108 CFU/mL) was observed with 2% FPH supplementation. In comparison, the caecum yielded the highest population (1.22 × 108 CFU/mL) under 1.5% FPH. Giving 2% FPH  to broiler chicken feed provides a weight gain of 1.021 kg/head. The primary characteristics of the eight bacterial colony isolates suspected of being LAB were Gram-positive, catalase-negative, and did not form endospores. Eight LAB isolates of probiotic candidates were non-pathogenic as indicated by the occurrence of α-hemolysis and γ-hemolysis. Biochemical identification of probiotic candidates yielded four types of Lactobacillus, namely L. mucosae, L. frumenti, L. sanfranciscensis, and L. ferintoshensis. These LAB strains show promising probiotic potential for use as a feed additive in the broiler production system.